2021
DOI: 10.52543/tjpp.16.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Grapevine Virus D in Tunisia

Abstract: The prevalence and the genetic diversity of grapevine virus D (GVD) isolates from rootstocks, wine and table grape varieties grown in Tunisia were studied. RT-PCR assays performed on the coat protein gene (CP) showed the presence of GVD in 31.5% of the 403 samples tested. The highest rate of infection was found in table grapes (56.5%), followed by autochthonous table grapes (24.1%), wine grapes (20.8%) and rootstocks (12.5%). Sequences and phylogenetic analyses of the partial CP genes 14 GVD isolates showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Phylogenetic typing confirmed the prevalence of molecular group IV in the vineyards of southern Russia, whereas group I was less prevalent. For comparison, the absolute majority of isolates in Tunisia (70%) belonged to group I, while group IV was the second most prevalent [35]. The prevalence of group I was also reported in Turkey, Iran, and Slovakia [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic typing confirmed the prevalence of molecular group IV in the vineyards of southern Russia, whereas group I was less prevalent. For comparison, the absolute majority of isolates in Tunisia (70%) belonged to group I, while group IV was the second most prevalent [35]. The prevalence of group I was also reported in Turkey, Iran, and Slovakia [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The closest were isolates from South Africa. This molecular group is the most widespread in Slovakia, Turkey, Iran, and Tunisia [83][84][85][86]. Moreover, when we examined the coat protein gene of isolates detected in our previous studies in the Krasnodar Krai and the Republic of Crimea, we also identified isolates of GVA molecular groups II and IV [34,35].…”
Section: Family: Betaflexiviridaementioning
confidence: 99%